Evaluasi Kesesuaian Sarana dan Prasarana di Perumahan Relokasi Pasca Bencana Kelurahan Pandu - Watung, Christania H. T.; Pakasi, Sandra E.; Rengkung, Leonardus Ricky (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to evaluate the adequacy of facilities and infrastructure in the post-disaster relocation housing area in Pandu Sub-district, Manado City, and to identify unmet needs based on the Indonesian National Standard (SNI) 03-1733-2004 concerning Guidelines for Urban Housing Environment Planning. The background of this research stems from the low occupancy rate and public complaints regarding the availability of facilities and infrastructure in the relocation area. The methods employed in this study include descriptive quantitative analysis, evaluative analysis, and spatial analysis using the Network Analyst approach within a Geographic Information System (GIS) framework. A gap analysis was conducted by comparing the existing conditions with the provisions set out in the SNI. The results indicate that several facilities, such as the sub-district office, security post, health center, and parks, are in a state of disrepair or abandonment. Additionally, infrastructure components such as roads, drainage systems, and wastewater networks do not yet meet the established technical standards. Based on the findings, the study recommends improving the quality and quantity of facilities and infrastructure and reorganizing those that are not in compliance with the applicable SNI standards.